The Relationship Between Children's Problematic Internet-related Behaviors and Psychological Distress During the Onset of the COVID-19 Pandemic: A Longitudinal Study - Chen, Chao-Ying; Chen, I-Hua; Hou, Wen-Li; Potenza, Marc N; O'Brien, Kerry S; Lin, Chung-Ying; Latner, Janet D (Journal of addiction medicine, 2022)
The outbreak of the coronavirus disease 2019 (COVID-19) pandemic has generated negative effects on psychological well-being worldwide, including in schoolchildren. Government requirements to stay at home and avoid social and school settings may impact psychological well-being by modifying various behaviors such as problematic phone and Internet use, yet there is a paucity of research on this issue. This study examined whether the COVID-19 outbreak may have impacted problematic smartphone use (PSU), problematic gaming (PG), and psychological distress, specifically the pattern of relationships between PSU, PG, and psychological distress in schoolchildren. Longitudinal data on psychological distress, PSU, and PG were collected from 575 children in primary schools in 3 waves: Waves 1 and 2 were conducted before the COVID-19 outbreak and Wave 3 during the outbreak. Cross-lagged panel models were used to examine relationships between factors across the 3 waves. Cross-lagged models found that higher levels of PSU were not significantly related prospectively to greater psychological distress before the COVID-19 outbreak, but this prospective relationship became significant during the COVID-19 outbreak. Whereas PG was associated prospectively with psychological distress before the COVID-19 outbreak (ie, between Waves 1 and 2), this association became nonsignificant during the COVID-19 lockdown (ie, between Waves 2 and 3). The COVID-19 outbreak has seemed to change prospective relationships between PSU and psychological distress and PG and psychological distress in schoolchildren. Future research should examine whether restrictions on or information provided to schoolchildren may exacerbate PSUs effects on psychological distress.